ASSERTIVE BEHAVIOUR AND SELF ESTEEM AMONG ADOLESCENT GIRLS - Sonia Rani (Indian Journal of Psychiatric Nursing, 2017)
As adolescent health has become an increasingly important focus for governments, foundations, and behavioral researchers in contrast to other age groups. Mortality and morbidity rates for 10-25 year olds have been increasing in the past few decades. Self esteem is the most dominant and powerful predictor of happiness and life satisfaction but it is estimated that up to a half of adolescents will struggle with low self esteem and research had shown that, teens self esteem levels drop markedly in girls more than boys. To study the effectiveness of assertiveness training on self esteem and assertive behavior among adolescent girls of selected government schools, investigator developed a conceptual framework based on the Nola Pander's Health Promotion Model. The research approach adopted for the present study is a quantitative approach and the design selected was a quasi-experimental design (non equivalent pre test post test control group). Purposive sampling technique used to gather 40 adolescent girls in experimental and control group each. Data collected using socio-demographic variables and with standardized Rosenberg self esteem scale (r=0.94) and Rathus assertiveness schedule(r=0.732). Assertiveness training given for 5 days and post test-1 done after 15 days. Then the investigator administered the same intervention to the wait list control group. Post test-2 in experimental group assessed after two months of intervention. The mean post test-1 self esteem score in experimental group was 20.78 as compared with the mean post test self esteem score in control group was 13.55. The mean difference found was 7.225. Secondly, considering for assertive behavior mean post test-1 score in experimental group was 23.28 as compared with mean post test assertive behavior score in control group −4.23 and the mean difference shown 27.5. While comparing the post test-1 and post test-2 in experimental group, both self esteem and assertive behavior increased a little. It is concluded that the assertiveness training is effective in building the level of self esteem as well as improving the assertive behavior among adolescent girls and the findings also reveals that it improve while time progress.